Zinc is a transmembrane agonist that induces platelet activation in a tyrosine phosphorylation-dependent manner. Issue 1 (5th October 2015) - Watson, Ben R.; White, Nathan A.; Taylor, Kirk A.; Howes, Joanna-Marie; Malcor, Jean-Daniel M.; Bihan, Dominique; Sage, Stewart O.; Farndale, Richard W.; Pugh, Nicholas
Abstract : Exogenous zinc induces full aggregation of washed platelet suspensions. Zinc-induced aggregation is biphasic, suggestive of secondary signalling-mediated activation. Abstract : Following platelet adhesion and primary activation at sites of vascular injury, secondary platelet activation is induced by soluble platelet agonists, such as ADP, ATP, thrombin and thromboxane. Zinc ions are also released from platelets and damaged cells and have been shown to act as a platelet agonist. However, the mechanism of zinc-induced platelet activation is not well understood. Here we show that exogenous zinc gains access to the platelet cytosol and induces full platelet aggregation that is dependent on platelet protein tyrosine phosphorylation, PKC and integrin αIIb β3 activity and is mediated by granule release and secondary signalling. ZnSO4 increased the binding affinity of GpVI, but not integrin α2 β1 . Low concentrations of ZnSO4 potentiated platelet aggregation by collagen-related peptide (CRP-XL), thrombin and adrenaline. Chelation of intracellular zinc reduced platelet aggregation induced by a number of different agonists, inhibited zinc-induced tyrosine phosphorylation and inhibited platelet activation in whole blood under physiologically relevant flow conditions. Our data are consistent with a transmembrane signalling role for zinc in platelet activation during thrombus formation.